Capital Mobility and Exchange Market Intervention in Developing Countries - Rojas-Suárez, Liliana (International Monetary Fund, 1996)
Official controls on interest rates and capital flows rule out the use of traditional interest rate parity conditions to measure changes in the degree of capital mobility confronting developing countries. This paper develops an alternative technique for measuring the cost of undertaking disguised capital flows when such official controls are present. This measure is derived from an intertemporal, optimizing model of an open economy incorporating the influence of the authorities' foreign exchange market activities. The paper suggests that the real cost of undertaking disguised capital flows declined on average by nearly 70 percent between the early 1970s and the late 1980s